Penggunaan Media Interaktif Berbasis PowerPoint dengan Pendekatan Deep Learning Dalam Meningkatkan Minat dan Pemahaman Belajar - Rohainiah Zain; Arya Arostegi; Ely Suliastri; Yusrianti Yusrianti; Elvina Elvina (SEMESTA: Jurnal Ilmu Pendidikan dan Pengajaran, 2026)
This study aims to determine the effectiveness of using PowerPoint-based interactive media with a Deep Learning approach in increasing the learning interest and understanding of ninth-grade students in social studies. The use of engaging, dynamic, and responsive digital media is expected to create a more enjoyable learning atmosphere and improve students' deep thinking skills. This study was conducted in the 2025/2026 academic year with ninth-grade students as subjects. The results showed that the use of interactive media was able to significantly increase students' learning interest and strengthen conceptual understanding.